Completeness and capture rate of publicly funded arthroplasty procedures in the New Zealand Joint Registry. Issue 12 (2nd November 2020) - Rahardja, Richard; Allan, Rachele; Frampton, Christopher M.; Morris, Arthur J.; McKie, John; Young, Simon W.
ABSTRACT: Background: Registry‐based studies have become more common due to the availability of a large study cohort. However, the validity of findings is dependent on the completeness of the registry. This study aimed to validate the capture rate of the New Zealand Joint Registry (NZJR) by matching procedures that have been recorded separately via clinical coding by the New Zealand Government's National Surgical Site Infection Improvement Programme (SSIIP). Methods: The National Health Index, a unique identification code for all patients, was combined with the arthroplasty procedure performed (primary total knee arthroplasty (TKA), primary total hip arthroplasty (THA), revision TKA or revision THA) and operation side. Publicly funded procedures recorded in the NZJR were matched with procedures recorded by the SSIIP on a record‐by‐record basis. This identified the total number of arthroplasty procedures performed in New Zealand, which was used as the denominator value to calculate the procedure capture rate of the NZJR. Results: Between 2013 and 2018, 24 556 primary TKA, 28 970 primary THA, 2107 revision TKA and 4263 revision THA procedures were recorded by both datasets. The NZJR recorded 95.5% of primary TKA procedures, 96.3% of primary THA procedures, 97.1% of revision TKA procedures and 95.2% of revision THA procedures. Conclusion: The NZJR recorded >95% of publicly funded arthroplasty procedures. In contrast, there were inaccuracies in clinical coding by hospitals, particularly with revision procedures, demonstrating the benefits of an arthroplasty registry. However, data recorded by an infection surveillance programme may supplement arthroplasty registry data to strengthen the quality of research. Abstract : Clinical coding of arthroplasty procedures by hospitals may be inaccurate. In contrast, the New Zealand Joint Registry has high completeness and records >95% of knee and hip arthroplasty procedures.